2019
DOI: 10.1111/josh.12717
|View full text |Cite
|
Sign up to set email alerts
|

The Patterns of Moderate to Vigorous Physical Activity and Physical Education Enjoyment Through a 2‐Year School‐Based Program

Abstract: BACKGROUND:In this study, we examined the development of children's moderate to vigorous physical activity (MVPA) and physical education (PE) enjoyment through the Physical Activity as Civil Skill Program 2012-2014. METHODS:Participants were 661 (265 intervention, 396 control) elementary school children in central and northeast Finland.The program was implemented across 2 years with 3 measurement phases using self-reported MVPA and PE enjoyment, and accelerometer-determined MVPA of a random subsample (N = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 49 publications
(93 reference statements)
0
44
0
1
Order By: Relevance
“…Six studies were conducted in North America [38][39][40][41][42][43], five studies in Europe [44][45][46][47][48], one in Singapore [49] and one in New Zealand [50]. Sample sizes ranged from 15 [39] to 1519 [43], and the duration of interventions ranged from three weeks [46] to three years [45].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies were conducted in North America [38][39][40][41][42][43], five studies in Europe [44][45][46][47][48], one in Singapore [49] and one in New Zealand [50]. Sample sizes ranged from 15 [39] to 1519 [43], and the duration of interventions ranged from three weeks [46] to three years [45].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The analysis of study quality revealed one study classified as strong [43], nine studies as moderate [39][40][41][42][44][45][46]48,50] and three studies as weak [38,47,49]. Due to missing documentation of confounders prior to the intervention or insufficient control of confounders, most of the studies resulted in a weak rating.…”
Section: Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations